2013
DOI: 10.5152/balkanmedj.2013.7328
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Telomerase Enzyme Activity in Benign and Malignant Gynaecologic Pathologies

Abstract: Background: Telomeres are essential for the function and stability of eukaryotic chromosomes. Telomerase consists of three subunits: human telomerase reverse transcriptase (hTERT), human telomerase RNA (hTR), and telomerase protein 1 (TP1). The hTERT subunit determines the activity of telomerase as an enzyme and is detected in most human tumors and regenerative cells. Telomerase activity is a useful cancer-cell detecting marker in some types of cancers.Aims: The aim of this study was to assess of telomerase hT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The authors also noted that telomerase activity was increased by estrogen which induced cell proliferation and was reduced in progesterone dominant conditions, indicative of an ovarian steroid hormonal regulation. The finding of high telomerase activity in endometrial cancers has been subsequently confirmed by many other groups (15, 25, 159, 239, 247, 267269). In addition to the high telomerase activity measured by the gold standard test, the TRAP assay, some authors studied expression levels of components of the telomerase holoenzyme using qPCR to detect gene expression levels.…”
Section: Endometriumsupporting
confidence: 53%
“…The authors also noted that telomerase activity was increased by estrogen which induced cell proliferation and was reduced in progesterone dominant conditions, indicative of an ovarian steroid hormonal regulation. The finding of high telomerase activity in endometrial cancers has been subsequently confirmed by many other groups (15, 25, 159, 239, 247, 267269). In addition to the high telomerase activity measured by the gold standard test, the TRAP assay, some authors studied expression levels of components of the telomerase holoenzyme using qPCR to detect gene expression levels.…”
Section: Endometriumsupporting
confidence: 53%
“…Previous research has demonstrated high telomerase activity in the premenopausal endometrium, with a transition to low or undetectable levels in the postmenopausal endometrium [ 36 , 38 , 39 ]. Despite unique endometrial telomerase biology, there is reactivation of telomerase activity from the postmenopausal state to EC [ 28 , 29 , 35 , 40 ]. Hence, telomerase must factor in the malignant transformation of the endometrium.…”
Section: Introductionmentioning
confidence: 99%